Modeling and simulation of new configuration of dynamic voltage restorer for power quality improvement - Omar, Rosli; Rahim, nasrudin (SAGE PUBLICATION, 2011)
The Dynamic Voltage Restorer (DVR) is a custom device that is used to maintain the voltage at the load terminals from various power quality problems due to distort of supply voltage in the network. In this paper, a novel control strategy is described for mitigation of voltage sags and swells on sensitive loads. The (DVR) has become popular as a cost effective solution for the protection of sensitive loads from voltage sags and swells. The new control of the compensation voltages in DVR, based on dqo algorithm, is discussed. The MATLAB/SIMULINK SimPower System toolbox has been used to obtain simulation results in order to verify the proposed scheme. From the results, it shows that the DVR is able to compensate the voltage sag or swell at sensitive loads by injecting an appropriate voltage through injection transformer.